Modification of chia (Salvia hispanica L.) seed mucilage (a heteropolysaccharide) by atmospheric pressure cold plasma jet treatment - Mutlu, Sebnem; Palabiyik, Ibrahim; Kopuk, Berkay; Gunes, Recep; Boluk, Esra; Bagci, Ufuk; Ozmen, Duygu; Toker, Omer Said; Konar, Nevzat (ELSEVIER, 2023)
Chia seeds (CS) were subjected to atmospheric pressure cold plasma jet (APCPJ) for different times (30, 60, and 120 s) by using argon gas, and then chia mucilage (CM) was extracted from the seeds to investigate the technological properties of mucilage (a heteropolysaccharide). The gel samples prepared from dried CM obtained from CS treated with 30 s and 120 s APCPJ showed noticeably higher consistency index of 11.43 and 13.63 Pa.sn, while the control and 60 s APCPJ showed a lower consistency index of 1.07 and 0.35, respectively. HerschelBulkley was better at defining the flow behavior of CM gels, and the treatment increased the shear-thinning and consistency properties. Moreover, CM gels of APCPJ-treated seeds (30 s and 120 s) showed higher elastic properties and better resistance against deformation. The treatment induced cross-linking between polysaccharide chains as confirmed by FTIR, and SEM micrographs demonstrated that APCPJ caused etching on the surface of seeds, thus a more compact structure was obtained in the hydrated mucilage samples depending on the APCPJ time. The highest treatment time (120 s) decreased the solubility, and the water (15%) and oil holding capacity (25%), while it did not significantly affect the emulsion ability and stability. In conclusion, it was found that the APCPJ improved the viscosity and elastic features of CM gels by cross-linking and strengthening the polymer network, which may provide opportunities to use this gum in new food applications.
Keywords: Cold plasma; Polysaccharides; Cross -linking; FUNCTIONAL-PROPERTIES; PHYSICOCHEMICAL PROPERTIES; RHEOLOGICAL PROPERTIES; CHEMICAL-COMPOSITION; STARCH; GUM; EXTRACTION; YIELD; Food Science & Technology